Geeks and the Holy Grail - Mancusi, Mari (Mancusi, Mari. Camelot code, 2020)
Twelve-year-old Sophie Sawyer is a Camelot Companion, tasked with protecting the King Arthur legend. Her first mission is to help a young druid and Merlin's thirteen-year-old apprentice protect the Holy Grail from the sorceress Morgana.